Density Functional Theory Calculations of Nuclear Material Properties in the Creation of a Closed Fuel Cycle: A Short Review - Alexander Y. Galashev (Energy Material Advances)
The wasteful use of fission energy must be changed by new technologies, including the creation of a closed nuclear fuel cycle. Recovered recycled fuel from thermal reactors will be used in fast neutron reactors. Due to their 5f electrons, actinides have unique properties, including strong electron correlations and strong spin-orbit interactions. Despite their attractiveness, experimental study of such systems is limited due to their toxicity, radioactivity, and reactivity. Theoretical modeling plays a particularly valuable role in the study of actinides and their compounds. Density functional theory (DFT) with Hubbard U-correction has become widespread because this approach produces reasonable predictions with minimal computational effort. In fact, DFT is the only theory that applies to all materials in nuclear technology, from the lightest to the heaviest elements. We believe that this work represents the most important DFT studies on nuclear fuel properties, resulting in the development of the closed nuclear cycle currently being created. This review reflects the main directions of DFT studies of the physical properties of actinides with an emphasis on the development of spent nuclear fuel recovery technology. Attention is paid to the calculation of mechanical, thermal, and magnetic properties, as well as the analysis of the structure of nuclear fuel with high radiation stabilities. Problems of DFT modeling are considered. The obtained data expand the understanding of the physicochemical properties of spent nuclear fuel and contributes to the development of technology for its reprocessing.